2013
DOI: 10.1037/a0029430
|View full text |Cite
|
Sign up to set email alerts
|

Goal conflict and goal facilitation as predictors of daily accelerometer-assessed physical activity.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractObjective: To test whether perceptions of conflicting and facilitating personal goals, and actual daily time spent in their pursuit, predict accelerometer-assessed physical activity (PA). Methods: A prospective multi-level design with a daily accelerometer-based assessment of PA over one week was used (N=106). Participants' personal goals were elicited using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 30 publications
7
81
1
Order By: Relevance
“…Fourth, we directly compared goal priority and goal conflict, with data across all four studies pointing to the stronger moderating effects of the former. Fifth, in addition to showing these effects for the previously studied behavior of physical activity (Studies 1-3; Li & Chan, 2008;Presseau et al, 2010Presseau et al, , 2011Presseau et al, , 2013 we showed the effects are similar for a broader range of health protective and risk behaviors (Study 4). Sixth, in contrast to Li and Chan (2008), we…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Fourth, we directly compared goal priority and goal conflict, with data across all four studies pointing to the stronger moderating effects of the former. Fifth, in addition to showing these effects for the previously studied behavior of physical activity (Studies 1-3; Li & Chan, 2008;Presseau et al, 2010Presseau et al, , 2011Presseau et al, , 2013 we showed the effects are similar for a broader range of health protective and risk behaviors (Study 4). Sixth, in contrast to Li and Chan (2008), we…”
Section: Discussionmentioning
confidence: 93%
“…Third, we show these effects hold when controlling for the effects of past behavior (Studies 2-4; see also Li & Chan, 2008) and when using an objective measure of behavior (see also Presseau et al, 2013) and past behavior (Study 3). Relatedly we also support previous research in showing goal effects in both between-subjects (Presseau et al, 2010) and within-subjects (Presseau et al, 2013) GOAL MEASURES AND THE INTENTION-BEHAVIOR LINK 23 designs. Fourth, we directly compared goal priority and goal conflict, with data across all four studies pointing to the stronger moderating effects of the former.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers refer to the Personal Projects Analysis (PPA) theory (Little & Gee, 2007), in which objectives are assessed based on five factors: project meaning (satisfaction, self-identification, value congruency), structure (control, time, initiation, positive/ negative influence), community (visibility to others, importance assessment by others), efficacy (chances for accomplishment, progress, skills), and stress (challenge, stress, level of difficulty). The tool has been used to test whether perceptions of conflicting and facilitating personal goals, and actual daily time spent in their pursuit, predict accelerometer-assessed physical activity (Presseau, Tait, Johnston, Francis, & Sniehotta, 2013). The importance of time for goaloriented behaviour was stressed by Feather and Bond (1994), who developed the Time Structure Questionnaire, which concerns such aspects of time use as organization, purpose, routine, planning, inertia, and daydreaming.…”
Section: Inventory Of Physical Activity Objectivesa New Methods Of Meamentioning
confidence: 99%